The Effects of Anapanasati with Biofeedback on The Stress of Amphetamine Patiens’ Primary Caregivers: The Effects of Anapanasati with Biofeedback on The Stress of Amphetamine Patiens’ Primary Caregivers. - Hancomthaun, Dawan; Somprasert, Chomchuen; Jirarode, Angkana (Journal of The Royal Thai Army Nurses, 2023)
The purpose of this Quasi-experimental research was to determine the effects of Ānāpānasati with biofeedback on the stress of amphetamine patients’ primary caregivers. The sample consisted of 60 caregivers of amphetamine patients, recruited using the inclusion criteria. They were randomly assigned to the control and experimental groups, with 30 subjects in each group. The experimental group received the Ānāpānasati with biofeedback created by the researchers. It consisted of eight sessions 90 minutes each, one time per week, for a total of eight weeks. The control group received routine caring activities. The research instruments were the following: 1) a general information questionnaire; 2) Ānāpānasati with biofeedback validated for content by three qualified persons; and 3) the Thai Stress Test (TST), which examined the questionnaire’s reliability, with a Cronbach’s alpha coefficient of .84. The demographics were analyzed using descriptive statistics. A comparison of the mean negative and positive stress scores of the primary caregivers of amphetamine addicts between the pretest and posttest for the experimental group was analyzed using dependent t-test. Further, an independent t-test was used to examine the mean difference in the negative and positive mean scores for the pretest and posttest for the experimental and control group. The results of the findings were as follows: 1) The experimental group participants had a lower post-experimental negative stress mean score (M=13.43, SD=1.96) than the pre-experimental negative stress mean score (M=21.27, SD=4.23), which was statistically significant (t=8.95, p<.001). After the experiment, it was found that the experimental group had a statistically significantl higher positive stress mean score (M=22.70, SD=2.55) than before the experiment at (M=11.33, SD=5.77) and (t =11.05, p<.001) respectively. 2) The mean difference of negative stress mean score in the caregivers of amphetamine addicts between the pretest and posttest of the experimental group that participated in the Ānāpānasati with biofeedback program ( =7.84, SD=4.80) were significantly greater than the mean difference of negative stress mean score of the control group that received routine caring activities (=0.27, SD=0.91) (t=8.50, p<.001), and the mean difference of positive stress mean score in the caregivers of amphetamine addicts between the pretest and posttest of the experimental group (3=11.37, SD=5.61) was significantly greater than that of the control group that received routine caring activities (4=0.03, SD=1.07) (t=10.83, p<.001). As a result of this study, it can be concluded that the Ānāpānasati with biofeedback can reduce stress in primary caregivers of amphetamine patients.